Direito e moralidade: argumentos a favor da (tese da)conexão necessária - Matos, Daniel Ortiz (Universidade do Vale do Rio dos Sinos, 2019)
This work is a defense of the (thesis) necessary connection between Law and Morality based on the Hermeneutic tradition. Faced with the complexity of the legal phenomenon, our apology is substantiated on an argumentative plurality, in order to demonstrate in diverse ways and forms how this connection is constituted. In order to do so, we establish dialogues and some debates, especially with those who defend the necessary (conceptual) separation thesis. For us, this research is significant because of the role of Law in society. In ordaining common life, coexistence, juridical is instituted in and from of moral experience. And this, in turn, occurs through the moral imagination that we share. Thus, both the form and content of Law are morally constituted. In other words, it establishes a differentiated moral reality in which we are from before being born and we keep after our departure. Therefore, properly understanding the limits and possibilities of the necessary connection between Law and Morality is more than an epistemic effort, it is an ethical imperative.
Keywords: Direito; Moralidade; Conexão; Separação; Justiça; Law; Morality; Connection; Separation; Justice; ACCNPQ::Ciências Sociais Aplicadas::Direito